ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERBEDAAN PRESTASI BELAJAR SISWA PADA SEKOLAH DASAR NEGERI DAN SWASTA DI DISTRIK MIMIKA BARU - Anna Gracia Lasol; Rullan L Manduapessy (CV. ADIBA AISHA AMIRA, 2026)
This study aims to determine the differences in student learning achievement influenced by internal and external factors in public and private primary schools in the Mimika Baru district, to determine the extent of the impact of Basic Education Institutions on social change in Mimika Regency, particularly in the Mimika Baru District. The research method used is a descriptive research method, which is a method used to analyse the factors that influence differences in student learning achievement at public and private primary schools in the Mimika Baru district. In this study, the data collection methods used were questionnaires, observation, and literature study. To determine the differences in student achievement influenced by internal and external factors, the analysis instrument used in this study was the Two-Sample Chi-Square analysis. The results of this study show that the factors that greatly influence student learning achievement in public and private elementary schools in the Mimika Baru district are external factors (from outside the students). In this analysis, we did not compare learning achievement between public and private elementary schools, but rather the factors that influence student or learner achievement.